Reichen Gesetze gegen trickreiche digitale Nutzerschnittstellen? Politischer Handlungsbedarf bei Dark Patterns; Dark patterns in web user interfaces: Toward an incentive-based policy approach supplementing legal provisions - Torsten J. Gerpott (Wirtschaftsdienst, 2022)
Immer wieder werden auf der EU-Ebene und in den EU-Mitgliedstaaten neue Gesetze geschaffen, die unfaire Designmuster bei Nutzeroberflächen auf Websites vor allem durch Verbote beseitigen sollen. Diese legalistische Politik erfordert jedoch Ergänzungen, die von der Bundesregierung bislang nicht mit ausreichender Durchschlagskraft in Angriff genommen worden sind. – – EU and national legislators in the EU continue to generate new regulations, striving to eliminate unfair design patterns in e-commerce, social media and other website user interfaces. This article briefly summarises relevant legal provisions and shows why, despite them, dark design patterns are still frequently found. It concludes that a move beyond a narrow legal dark pattern counter-strategy is required by setting incentives for website providers to implement bright interface design features voluntarily. In Germany, Government support has not been adequate and therefore requires improvement.
Keywords: D18; K20; L81; 330; Website; Benutzerschnittstelle; EU-Recht